2019
DOI: 10.1159/000495946
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Cardiac Biomarkers in the Setting of Kidney Disease

Abstract: Cardiovascular disease is prevalent in patients with chronic kidney disease (CKD) and responsible for approximately half of all CKD-related deaths. Unfortunately, the presence of CKD can lead to a challenging interpretation of cardiac biomarkers essential in accurate diagnosis and prompt management of heart failure and acute coronary syndrome. There is growing interest in novel cardiac biomarkers that may improve diagnostic accuracy reflecting myocardial injury, inflammation, and remodeling. Interpretation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 56 publications
2
26
1
Order By: Relevance
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
“…It is plausible that cardiovascular disease (CVD) and chronic kidney disease (CKD) are closely interrelated with each other, and patients with CKD have a strong risk of CVD [115,116]. It is well known that CKD is prevalent in patients with CVD and responsible for approximately half of all CKD-related deaths [26]. Thus, patients with end-stage CKD are at much higher risk of mortality due to CVD.…”
Section: Cardiovascular Disease and Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of maximal exercise performance is well-established in CKD [1][2][3], but less is known about its determinants. Elevated troponin T has been shown to be associated with increased cardiovascular mortality in end stage kidney disease (ESKD) [4][5][6]. The Food and Drug Administration has approved the use of troponin T (TnT) for identifying high mortality risk in CKD patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration has approved the use of troponin T (TnT) for identifying high mortality risk in CKD patients [5]. N-terminal pro-B-type natriuretic peptide (proBNP) elevation may occur in CKD independent of heart failure [4], but usually re ects underlying heart disease such as left ventricular hypertrophy or coronary atherosclerosis [7,8]. proBNP has been associated with cardiovascular events and cardiovascular mortality in CKD [9].…”
Section: Introductionmentioning
confidence: 99%